Skin‐Like Stretchable Fuel Cell Based on Gold‐Nanowire‐Impregnated Porous Polymer Scaffolds. Issue 39 (30th August 2020) - Gong, Shu; Du, Shengrong; Kong, Jianfei; Zhai, Qingfeng; Lin, Fenge; Liu, Siyuan; Cameron, Neil R.; Cheng, Wenlong
Abstract: Skin‐like energy devices can be conformally attached to the human body, which are highly desirable to power soft wearable electronics in the future. Here, a skin‐like stretchable fuel cell based on ultrathin gold nanowires (AuNWs) and polymerized high internal phase emulsions (polyHIPEs) scaffolds is demonstrated. The polyHIPEs can offer a high porosity of 80% yet with an overall thickness comparable to human skin. Upon impregnation with electronic inks containing ultrathin (2 nm in diameter) and ultrahigh aspect‐ratio (>10 000) gold nanowires, skin‐like strain‐insensitive stretchable electrodes are successfully fabricated. With such designed strain‐insensitive electrodes, a stretchable fuel cell is fabricated by using AuNWs@polyHIPEs, platinum (Pt)‐modified AuNWs@polyHIPEs, and ethanol as the anode, cathode, and fuel, respectively. The resulting epidermal fuel cell can be patterned and transferred onto skin as "tattoos" yet can offer a high power density of 280 µW cm −2 and a high durability (>90% performance retention under stretching, compression, and twisting). The results presented here demonstrate that this skin‐thin, porous, yet stretchable electrode is essentially multifunctional, simultaneously serving as a current collector, an electrocatalyst, and a fuel host, indicating potential applications to power future soft wearable 2.0 electronics for remote healthcare and soft robotics. Abstract : A skin‐like stretchable fuel cell is demonstrated using ultrathin gold nanowire impregnated porous polymerized high internal phase emulsions' (polyHIPEs) scaffolds. This epidermal fuel cell can be patterned and transferred onto human skins as "tattoos" yet can offer high stretchability and reasonably high power density, indicating potential applications to power next‐generation soft wearable 2.0 electronics for remote healthcare and soft robotics.